2003
DOI: 10.1002/chir.10262
|View full text |Cite
|
Sign up to set email alerts
|

Chiral HPLC separation and CD spectra of the C‐2 diastereomers of naringin in grapefruit during maturation

Abstract: Naringin is the chief flavanone glycoside of grapefruit (Citrus paradisi). It is responsible for part of the bitter taste of the fruit and can cause the inhibition of some cytochrome P450s. The direct separation of (2R)-and (2S)-naringin in the albedo of grapefruits was obtained in normal phase HPLC mode using Chiralcel OD as chiral stationary phase and n-hexane/ethanol with 0.1% of TFA as mobile phase. Chiralpak AD was almost ineffective in the separation. This procedure was used to evaluate the stereochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…The enzyme chalcone isomerase (CHI) R 1 = R 2 = R 3 = H, naringenin (1) R 1 = rhamnose (1→2) glucosyl, R 2 = R 3 = H, naringin (2) R 1 = H, R 2 = OH, R 3 = CH 3 , hesperetin (3) R 1 = rhamnose (1→6) glucosyl, R 2 = OH, R 3 = CH 3 , hesperidin (4) R 1 = rhamnose (1→2) glucosyl, R 2 = OH, R 3 = CH 3 , neohesperidin ( catalyzes the cyclization of chalcone with an apparent 100,000:1 preference for the synthesis of the (S)-isomer over the (R)-isomer (Jez, Bowman, Dixon, & Noel, 2000). As already mentioned, studies on citrus fruits revealed that flavanones and flavanones-7-O-glycosides are present as enantiomeric and epimeric mixtures, respectively, in different ratios depending on the maturity grade of the fruit (Caccamese et al, 2003;Gaffield et al, 1975;Gel-Moreto, Streich, & Galensa, 2001). More precisely, it was reported by Gaffield et al (1975) that the (2S)-isoform of naringin in grapefruit, the main form present in premature fruits, tends to convert to the (2R)-form, reaching an approximate epimeric ratio of about 3:2 at fruit maturity.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The enzyme chalcone isomerase (CHI) R 1 = R 2 = R 3 = H, naringenin (1) R 1 = rhamnose (1→2) glucosyl, R 2 = R 3 = H, naringin (2) R 1 = H, R 2 = OH, R 3 = CH 3 , hesperetin (3) R 1 = rhamnose (1→6) glucosyl, R 2 = OH, R 3 = CH 3 , hesperidin (4) R 1 = rhamnose (1→2) glucosyl, R 2 = OH, R 3 = CH 3 , neohesperidin ( catalyzes the cyclization of chalcone with an apparent 100,000:1 preference for the synthesis of the (S)-isomer over the (R)-isomer (Jez, Bowman, Dixon, & Noel, 2000). As already mentioned, studies on citrus fruits revealed that flavanones and flavanones-7-O-glycosides are present as enantiomeric and epimeric mixtures, respectively, in different ratios depending on the maturity grade of the fruit (Caccamese et al, 2003;Gaffield et al, 1975;Gel-Moreto, Streich, & Galensa, 2001). More precisely, it was reported by Gaffield et al (1975) that the (2S)-isoform of naringin in grapefruit, the main form present in premature fruits, tends to convert to the (2R)-form, reaching an approximate epimeric ratio of about 3:2 at fruit maturity.…”
Section: Resultsmentioning
confidence: 91%
“…95%, Sigma-Aldrich). It is known that commercial flavanones and glycoside derivatives are mixtures of enantiomers or epimers (Caccamese, Manna, & Scivoli, 2003;Uchiyama, Kim, Kawahara, & Goda, 2005). When measuring the NMR spectra of commercial naringin the presence of an additional set of signals belonging to second flavanone was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these preliminary investigations report the quantification of a variety of flavanones in citrus fruit juices and herbs [13,[28][29][30][31], or report the separation of flavanones on different stationary phases [27]. There is a paucity of investigations detailing the importance of stereospecific pharmacokinetics and pharmacodynamics of chiral flavanones.…”
Section: Introductionmentioning
confidence: 99%
“…Naringin is a �lavonoid from citrus fruits contributing to the bitter taste of grape fruits [1][2][3]. Effects of naringin include neuroprotection [4], inhibition of in�lammation [3], decrease of blood lipids [5], and inhibition of bone resorption [6].…”
Section: Introductionmentioning
confidence: 99%